(untitled) (ART AND CULTURE BULLETIN, 2026)
This scientific article explores the practical and theoretical foundations of scoring background noises, particularly underwater scenes, in the field of cinema, television, and radio sound directing. The use of hydrophones, the acoustic properties of water, and the digital processing of recorded audio signals during post-production are analyzed through examples of films such as, "War of the Worlds", and "Finding Nemo". The article serves as an important methodological guide for university students studying audio engineering and future sound directors.